Ethylene inhibits rice root elongation in compacted soil via ABA- and auxin-mediated mechanisms - Huang, Guoqiang; Kilic, Azad; Karady, Michal; Zhang, Jiao; Mehra, Poonam; Song, Xiaoyun; Sturrock, Craig J.; Zhu, Wanwan; Qin, Hua; Hartman, Sjon; Schneider, Hannah M.; Bhosale, Rahul; et al. (Proceedings of the National Academy of Sciences - PNAS, 2022)
Soil compaction represents a major agronomic challenge, inhibiting root elongation and impacting crop yields. Roots use ethylene to sense soil compaction as the restricted air space causes this gaseous signal to accumulate around root tips. Ethylene inhibits root elongation and promotes radial expansion in compacted soil, but its mechanistic basis remains unclear. Here, we report that ethylene promotes abscisic acid (ABA) biosynthesis and cortical cell radial expansion. Rice mutants of ABA biosynthetic genes had attenuated cortical cell radial expansion in compacted soil, leading to better penetration. Soil compaction-induced ethylene also up-regulates the auxin biosynthesis gene OsYUC8. Mutants lacking OsYUC8 are better able to penetrate compacted soil. The auxin influx transporter OsAUX1 is also required to mobilize auxin from the root tip to the elongation zone during a root compaction response. Moreover, osaux1 mutants penetrate compacted soil better than the wild-type roots and do not exhibit cortical cell radial expansion. We conclude that ethylene uses auxin and ABA as downstream signals to modify rice root cell elongation and radial expansion, causing root tips to swell and reducing their ability to penetrate compacted soil.